Studi Molecular Docking dan Evaluasi Farmakokinetik Senyawa Analog Pirazol Turunan Benzen-Sulfonilurea sebagai Inhibitor Enzim Aldose Reduktase and α-Glukosidase Menggunakan Pendekatan In Silico - Fatisa, Yuni; Utami, Lisa; Syahri, Jufrizal; Jasril, Jasril; Lazulva, Lazulva (Jurnal Riset Kimia, 2024)
The pyrazole scaffold modification in various chemical structures on several studies has shown various biopharmacological activities. This study aims to predict the potential inhibition of pyrazole analogs derived benzene-sulfonylurea (4A, 4B, 4E, 5A, 5C, 5D) against the α-glucosidase (3A4A) and aldose reductase (3RX2) enzymes based on a molecular docking approach using Molecular Operating Environment (MOE) 2020.0102 software and evaluate pharmacokinetic profile (ADMET). In this study, the six test compounds were obtained from previous studies that have been proven antihyperglycemic. The results showed that all the 3,5-disubstituted benzene-sulfonylurea derivative pyrazole analogs are predicted to have low inhibitory activity against the α-glucosidase enzyme. Further, all compounds showed good aldose reductase inhibitor activity and had lower binding free energy values ​​than tolrestat as the positive control (-6.82 kcal/mol). Compound 5C has the best potential inhibitory activity against the aldose reductase enzyme compared to the other test compounds, because it has the lowest binding free energy value (-8.76 kcal/mol) and interacts with important residues on the receptor forming four hydrogen bonds, namely the carbonyl group of SO2 with residues Trp111 and His110, and the carbonyl group of the amide with residues His110 and Tyr48, as well as 3 hydrophobic bonds, namely a pyrazole ring with residues Leu300, Trp219 and a furan ring with Phe122. ADMET properties of the compounds are also predicted. This information provides an opportunity for a 5C compound as an aldose reductase inhibitor agent to develop drug candidates with better and safer activities.